Prihvat i odlaganje objekta mobilnim robotom korištenjem vizualne povratne veze : završni rad - Čargonja, Neven (N. Čargonja, 2019)
Sažetak na hrvatskom: This thesis deals with the problem of detecting circular movement and calculating the distance between two marker stands with the help of the OptiTrack motion capture system. The first part explains the theoretical background needed to detect circular movement and calculate the distance. To check if the information from OptiTrack gives the circular movement first it is needed to find the plane of the points and rotate them to a two-dimensional coordinate system. Using the least squares method the circle parameters are calculated. Opti- Track gives the information about the top of the marker stand so to find the distance between the bottom of the two marker stands transformation must be applied. In the second part experimental setup and the given solution are described. Lastly, the results of the distances calculated in two different ways are compared.